Razlike in podobnosti v regionalnem razvoju Idrijskega in Zasavja - Kušar, Simon (Geografski vestnik, 2004)
The Idrijsko and Zasavje regions have common geographical features. Both regions belong to the hilly part of Slovenia. They have same microclimate and not adequate connection to the interior of the country. Mining industry caused concentration of population and activities. Today Zasavje is a problem region while Idrijsko is not. On the basis of comparison between regions according to selected features and comparative analysis of society in the past we are trying to find the answer why are we facing with different regional development situation in those two regions.
Keywords: Idrijsko; Central Sava Valley; Zasavje; regionalni razvoj; ekonomska geografija; regionalno gospodarstvo